Micro-raman investigation of si, ge and carbon related nanostructures - Wasyluk, Joanna (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2010)
The degradation in performance of silicon devices with scaling caused by fundamental silicon material limitations by the year of 2020 is forcing the semiconductor industry to consider extraordinary materials to replace silicon. Introducing new structures (like germanium on insulator), alteration of material properties in the channel region (such as SiGe alloys or strained Si), and replacement of Si (by graphene) are all being considered. Therefore a number of new materials are currently investigated by researches as a promising nano-material for "post-silicon electronics". The wide range of information on structural properties of these materials can be provided using Raman spectroscopic technique.
Keywords: Electronic & Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin.